Network Emulator Based on Openstack for the Implementation of a Virtual Data Network Laboratory in Higher Education Institutions - Terrel-Villanueva, Vasty; Burga-Durango, Daniel; Tello-Saenz, Carlos [UNESP] (Springer Nature, 2025)
Nowadays, networks are indispensable tools for the development of new technologies such as cloud computing, big data, the Internet of Things, among others. Therefore, it is necessary to explore new tools that allow improving the understanding and practical skills of students in the field of networks. This document presents a web application based on OpenStack, which allows for the emulation of physical network laboratories through the virtualization of components, as it partitions physical resources to provide access to more users. For this, some Openstack services were used in conjunction with VirtualBox. Additionally, validation was conducted through end users, and the results obtained showed that 94% of expert teachers and 95.8% of surveyed students highlighted the utility of the application, while 78% of teachers and 91.5% of surveyed students emphasized the usability of the developed application. These results demonstrate the potential of the application to be implemented in a virtual laboratory of a networking course and take advantage of the available technological resources.
Keywords: emulator; networking; openstack; virtual laboratory